ESTUDIO DE LAS ZOONOSIS PARASITARIAS DE LOCALIZACIÓN OCULAR EN EL INSTITUTO DE OFTALMOLOGÍA (INO) (PERIODO 1985-1999) - García S., Marco (2002)
The objective of the present study was to determine the frequency of parasitic zoonosis with ocular localization, diagnosed in the Institute of Ophthalmology (INO), which belongs to the Ministry ofHealth (MINSA) in Lima-Peru, between 1985 to 1999. The analysis of 4,843 histopathology records submitted to the Laboratory of Ocular Pathology between the years 1985 and 1999, showed that 0.47 ± 0.002% (23/4,843) corres-ponded to parasitic zoonosis; where the suggestive lesions of leishmaniosis, toxocaríosis andocularcysticercosis hada frequency of 34.8 ±0.19%, 30.4±0.19% and 17.4±0.15%, respectively. While the analysis carried out with 1,306 clinical records of patients who went to the U vea Service ofthe same institute between the years 1988 and 1999 showed that 22.3 ± 0.02% (291/1,306) suffered from sorne type of parasitic zoonosis being the · most frequent the uveitis dueto toxoplasma (88.7 ± 0.04% ), toxocariosis and the ocular cysticercosis (10.0 ± 0.03% and 1.4 ± 0.01 %). It was concluded that the histopatologic diagnosis showed a low frequency (0.47 ± 0.002%) of parasitic zoonosis; however, a high frequency exists in uveitis patients that attend the INO clinic (22.3 ± 0.02% ).